Sensitivity of mass spectrometry analysis depends on the shape of the filtration unit used for filter aided sample preparation (FASP). Issue 13 (3rd July 2016) - Lipecka, Joanna; Chhuon, Cerina; Bourderioux, Matthieu; Bessard, Marie‐Andrée; van Endert, Peter; Edelman, Aleksander; Guerrera, Ida Chiara
Abstract : Efficient protein solubilization using detergents is required for in‐depth proteome analysis, but successful LC‐MS/MS analysis greatly depends on proper detergents removal. A commonly used sample processing method is the filter‐aided sample preparation (FASP), which allows protein digestion and detergent removal on the same filtration device. Many optimizations of the FASP protocol have been published, but there is no information on the influence of the filtration unit typology on the detergents removal. The aim of this study was to compare the performance of conic and flat bottom filtration units in terms of number of proteins identified by LC‐MS/MS. We have analyzed 1, 10 and 100 μg of total cell lysate prepared using lysis buffer with different SDS concentrations. We compared the FASP protocol using conic and flat bottom filtration units to ethanol precipitation method. Subsequently, we applied our most performant protocol to single murine pancreatic islet, and identified up to 2463 protein using FASP versus 1169 proteins using ethanol precipitation. We conclude that FASP performance depends strongly on the filter shape: flat bottom devices are better suited for low‐protein samples, as they allow better SDS removal leading to the identification of greater number of proteins.